2020
DOI: 10.1016/j.ebiom.2019.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of ATP is a biomarker of HIV cognitive impairment

Abstract: Background: In developed countries, Human Immunodeficiency Virus type-1 (HIV-1) infection has become a chronic disease despite the positive effects of anti-retroviral therapies (ART), but still at least half of the HIV infected population shown signs of cognitive impairment. Therefore, biomarkers of HIV cognitive decline are urgently needed. Methods: We analyze the opening of one of the larger channels expressed by humans, pannexin-1 (Panx-1) channels, in the uninfected and HIV infected population ( n = 175). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 91 publications
5
48
0
Order By: Relevance
“…Prior data indicate that gp120 may induce the release of several "danger" signals from glial cells, including ATP [81], the latter molecule being recently proposed as a biomarker of HIV-1-mediated cognitive impairment [82]. With this in mind, two significant elements underscore the importance of ATP signaling on the gp120-induced astrocyte changes in our system.…”
Section: Discussionmentioning
confidence: 96%
“…Prior data indicate that gp120 may induce the release of several "danger" signals from glial cells, including ATP [81], the latter molecule being recently proposed as a biomarker of HIV-1-mediated cognitive impairment [82]. With this in mind, two significant elements underscore the importance of ATP signaling on the gp120-induced astrocyte changes in our system.…”
Section: Discussionmentioning
confidence: 96%
“…Our data indicate that HIV infection of astrocyte is not only important because it could be a viral reservoir but can amplify apoptosis, inflammation, and cellular dysfunction into neighboring uninfected cells, including neurons, endothelial cells, and other uninfected astrocytes (Eugenin et al, 2011;Orellana et al, 2014). We have previously demonstrated that HIV infection but not replication regulates expression of Connexin-43containing channels resulting in the maintenance of gap junctional communication between the few HIV-infected astrocytes and neighboring cells as well as the opening of hemichannels that contribute to the release of intracellular inflammatory mediators such as ATP and prostacyclin further contributing to the chronic inflammation observed in at least half of the HIV-infected population (Velasquez et al, 2020). Also, in vivo studies from our laboratory indicate that infected astrocytes can amplify CNS damage up to 300-500 µm away from the infected astrocytes clusters Malik et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, upon inflammation and damage, hemichannels become open and have been associated with several neurodegenerative disorders (Xing et al, 2019) including NeuroHIV (Eugenin et al, 2011a;Orellana et al, 2014;Berman et al, 2016;Eugenin, 2016, 2019). Only recently, we identified that circulating levels of ATP can be used to provide an early detection of cognitive impairment in HIV-infected individuals (Velasquez et al, 2020).…”
Section: Characteristic Of Glutamate Transportersmentioning
confidence: 99%